1
JEE Main 2019 (Online) 9th January Morning Slot
+4
-1
Out of Syllabus
The equation of the line passing through (–4, 3, 1), parallel

to the plane x + 2y – z – 5 = 0 and intersecting

the line $${{x + 1} \over { - 3}} = {{y - 3} \over 2} = {{z - 2} \over { - 1}}$$ is :
A
$${{x + 4} \over 3} = {{y - 3} \over {-1}} = {{z - 1} \over 1}$$
B
$${{x + 4} \over 1} = {{y - 3} \over {1}} = {{z - 1} \over 3}$$
C
$${{x + 4} \over -1} = {{y - 3} \over {1}} = {{z - 1} \over 1}$$
D
$${{x - 4} \over 2} = {{y + 3} \over {1}} = {{z + 1} \over 4}$$
2
JEE Main 2019 (Online) 9th January Morning Slot
+4
-1
Out of Syllabus
The plane through the intersection of the planes x + y + z = 1 and 2x + 3y – z + 4 = 0 and parallel to y-axis also passes through the point :
A
(–3, 0, -1)
B
(3, 2, 1)
C
(3, 3, -1)
D
(–3, 1, 1)
3
JEE Main 2018 (Online) 16th April Morning Slot
+4
-1
If the angle between the lines, $${x \over 2} = {y \over 2} = {z \over 1}$$

and $${{5 - x} \over { - 2}} = {{7y - 14} \over p} = {{z - 3} \over 4}\,\,$$ is $${\cos ^{ - 1}}\left( {{2 \over 3}} \right),$$ then p is equal to :
A
$${7 \over 2}$$
B
$${2 \over 7}$$
C
$$-$$ $${7 \over 4}$$
D
$$-$$ $${4 \over 7}$$
4
JEE Main 2018 (Online) 16th April Morning Slot
+4
-1
Out of Syllabus
The sum of the intercepts on the coordinate axes of the plane passing through the point ($$-$$2, $$-2,$$ 2) and containing the line joining the points (1, $$-$$1, 2) and (1, 1, 1) is :
A
4
B
$$-$$ 4
C
$$-$$ 8
D
12
EXAM MAP
Medical
NEET